Online Inclusive School: A Technological Breakthrough in Inclusive Education During the Covid-19 Period - Nurdyansyah Nurdyansyah; Moch Bahak Udin By Arifin; Ika Ratna Indra Astutik; Pandi Rais (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to develop an inclusive online school (OIS) to overcome the problem of the low learning competence of inclusive students, especially during the Covid-19 pandemic. The research method used the ADDIE model with the following steps: analyze, design, development, implementation, and evaluation to develop OIS in prototypes and learning steps. Research participants included students at the elementary school level in Indonesia. The instruments used in data collection are validation sheets and student learning competency tests. The data analysis technique used in this study is SPSS version 22.0 (IBM Corp. Released 2016) with a significance level of 0.05 with a paired sample t-test with p-value or sig. (2-tailed). The study results showed that OIS and its learning steps were feasible and appropriate to facilitate the learning competencies of inclusive students during the pandemic. The learning competence of inclusive students also increased significantly after the implementation of OIS. This research implies that OIS tools can be a technology-based breakthrough in inclusive education, focusing on limited classroom practice.